2015
DOI: 10.3892/ijmm.2015.2090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bombesin receptor subtype-3 and its synthetic agonist on signaling, glucose transport and metabolism in myocytes from patients with obesity and type 2 diabetes

Abstract: Bombesin receptor subtype-3 (BRS-3) is an orphan G-protein-coupled receptor (GPCR) member of the bombesin receptor family. Several studies have suggested an association between obesity, alterations in glucose metabolism, diabetes and the BRS-3 receptor. In this study, we focused on patients simultaneously diagnosed with obesity and type 2 diabetes (OB/T2D). The analysis of BRS-3 expression in the skeletal muscle of these patients revealed a marked decrease in the expression of BRS-3 at the mRNA (23.6±1.3-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Furthermore, in patients simultaneously diagnosed with obesity and type 2 diabetes, much lower BRS-3 mRNA levels in skeletal muscle are found, than that previously observed in patients affected by either T2D or obesity, which suggest a potential synergy in the negative impact of these two conditions on BRS—receptor expression[63]. In skeletal muscle myocytes from normals, patients with obesity or with type 2 diabetes mellitus, BRS-3-receptor activation results in stimulation of glucose transport, MAP kinase, p90SRSKI, protein kinase B, PI3K, p70s6 kinase, glycogen synthetase α activity and glycogen synthesis[59,63,64]. In addition the myocytes from patients with the two altered metabolic states alone or together, had increased sensitivity to BRS-3 stimulated glucose uptake and these intracellular cascades (Table 3) [59,63,64].…”
Section: Brs-3 In Obesity; Energy and Glucose Homeostasis And Diabmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, in patients simultaneously diagnosed with obesity and type 2 diabetes, much lower BRS-3 mRNA levels in skeletal muscle are found, than that previously observed in patients affected by either T2D or obesity, which suggest a potential synergy in the negative impact of these two conditions on BRS—receptor expression[63]. In skeletal muscle myocytes from normals, patients with obesity or with type 2 diabetes mellitus, BRS-3-receptor activation results in stimulation of glucose transport, MAP kinase, p90SRSKI, protein kinase B, PI3K, p70s6 kinase, glycogen synthetase α activity and glycogen synthesis[59,63,64]. In addition the myocytes from patients with the two altered metabolic states alone or together, had increased sensitivity to BRS-3 stimulated glucose uptake and these intracellular cascades (Table 3) [59,63,64].…”
Section: Brs-3 In Obesity; Energy and Glucose Homeostasis And Diabmentioning
confidence: 99%
“…Recently detailed studies have been reported of the comparative signaling cascades involved in BRS-3 activation in myocytes of diabetic, obese and normal subjects[59,63,64], and this will be discussed in a later section on role of BRS-3 in obesity, energy metabolism and glucose homeostasis.…”
Section: Brs-3 and The Mammalian Bnr Family (Table 1)mentioning
confidence: 99%
See 3 more Smart Citations